2017
DOI: 10.1152/ajpendo.00075.2017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sex steroids coregulate adipose tissue immune cell populations in healthy men

Abstract: Male hypogonadism results in changes in body composition characterized by increases in fat mass. Resident immune cells influence energy metabolism in adipose tissue and could promote increased adiposity through paracrine effects. We hypothesized that manipulation of circulating sex steroid levels in healthy men would alter adipose tissue immune cell populations. Subjects ( = 44 men, 19-55 yr of age) received 4 wk of treatment with the gonadotropin-releasing hormone receptor antagonist acyline with daily admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 90 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Recently, Rubinow and colleagues analyzed lymphocyte subsets in subcutaneous adipose tissue biopsies after 4 weeks of pharmacological testosterone suppression with a GnRH receptor antagonist and controlled testosterone replacement in healthy male subjects. In this clinical study, change in serum total testosterone levels correlated inversely with CD3 + , CD4 + , and CD8 + T cells and ATMs within adipose tissue ( 275 ).…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 68%
See 1 more Smart Citation
“…Recently, Rubinow and colleagues analyzed lymphocyte subsets in subcutaneous adipose tissue biopsies after 4 weeks of pharmacological testosterone suppression with a GnRH receptor antagonist and controlled testosterone replacement in healthy male subjects. In this clinical study, change in serum total testosterone levels correlated inversely with CD3 + , CD4 + , and CD8 + T cells and ATMs within adipose tissue ( 275 ).…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 68%
“…Estrogen protective action on glucose homeostasis is not only exerted in the pancreas; several studies indicated that estradiol enhances insulin sensitivity in peripheral tissues, improves body fat distribution, and reduces adipose tissue inflammation ( 273 275 ). Estrogen treatment prevented insulin insensitivity and reduced the expression of adipose tissue inflammation ( Mcp-1 and Cd68 ) induced by high-fat diet in ovariectomized mice ( 274 ).…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 99%
“…Thus, in obese men and women, no correlation was found between 17β-estradiol concentrations in plasma and visceral fat, and disproportionately elevated estradiol concentrations were found in adipose tissue relative to plasma in obese men [89] . Dissociations also were found between plasma and breast fatty tissue estrogen concentrations in women as well as plasma and subcutaneous adipose tissue estrogen concentrations in healthy men subject to experimental sex steroid manipulation [12] , [90] . Consequently, understanding the metabolic roles of sex steroid immunomodulation requires quantification of local, tissue-specific sex steroid concentrations, identification of the key cell types implicated in local sex steroid production, and delineation of the pathways that regulate sex steroid synthesis and metabolism within metabolic tissues.…”
Section: Steroidogenic Capacity Of Immune Cellsmentioning
confidence: 81%
“…Therefore, androgens may already influence the frequencies of T cells in vivo early in life. In adult men, there is a recent report of a negative correlation between CD3+, CD8+, and CD4+ T cells residing in adipose tissue and serum testosterone levels ( 69 ). Moreover, upon stimulation of healthy human PBMC with TLR8/9 ligands, secretion of IL-10 in male PBMC was higher than in female PBMC.…”
Section: Androgens and Human T Cellsmentioning
confidence: 99%